STUDI KOMPARASI TINGKAT PENGGUNAAN KAYU BAKAR PADA USAHA TAHU DI DESA KAMAL DAN WAIMITAL KABUPATEN SERAM BAGIAN BARAT - Mayada, Mayada; Siahaya, Troice E.; Iskar, Iskar (MARSEGU : Jurnal Sains dan Teknologi, 2026)
Rising fossil fuel prices have driven increased reliance on firewood as an alternative energy source in small industries, including tofu processing enterprises. This study aimed to compare firewood consumption levels at two tofu processing businesses in West Seram Regency using a quantitative comparative approach and multiple linear regression analysis. Results showed that Tahu AE Enterprise (steam boiler kiln) consumed 31.30 m³/year, while Tahu Mandiri Enterprise (open kiln) consumed 83.43 m³/year, totaling 114.73 m³/year. Boiling frequency was the most dominant factor influencing firewood consumption. The high consumption associated with open kilns indicates a need for improved combustion technology efficiency. From a forestry perspective, firewood demand at this scale risks threatening surrounding forest sustainability unless supported by sustainable community forest management and renewable energy diversification.